Natural Products Treat Colorectal Cancer by Regulating miRNA - Shuoxi Guo; Meiqi Chen; Shuangyang Li; Zijun Geng; Ye Jin; Da Liu (Pharmaceuticals, 2023)
Diseases are evolving as living standards continue to improve. Cancer is the main cause of death and a major public health problem that seriously threatens human life. Colorectal cancer is one of the top ten most common malignant tumors in China, ranking second after gastric cancer among gastrointestinal malignant tumors, and its incidence rate is increasing dramatically each year due to changes in the dietary habits and lifestyle of the world’s population. Although conventional therapies, such as surgery, chemotherapy, and radiotherapy, have profoundly impacted the treatment of colorectal cancer (CRC), drug resistance and toxicity remain substantial challenges. Natural products, such as dietary therapeutic agents, are considered the safest alternative for treating CRC. In addition, there is substantial evidence that natural products can induce apoptosis, inhibit cell cycle arrest, and reduce the invasion and migration of colon cancer cells by targeting and regulating the expression and function of miRNAs. Here, we summarize the recent research findings on the miRNA-regulation-based antitumor mechanisms of various active ingredients in natural products, highlighting how natural products target miRNA regulation in colon cancer prevention and treatment. The application of natural drug delivery systems and predictive disease biomarkers in cancer prevention and treatment is also discussed. Such approaches will contribute to the discovery of new regulatory mechanisms associated with disease pathways and provide a new theoretical basis for developing novel colon cancer drugs and compounds and identifying new therapeutic targets.